COMPOSIÇÃO GRAVIMÉTRICA DOS RESÍDUOS SÓLIDOS DOS ALUNOS DO CURSO DE ENGENHARIA AMBIENTAL E SANITÁRIA DA UEMS - DA SILVA, Vitoria Bitencourt; KONRADT-MORAES, Leila Cristina; BRAGA, Gabriel Bastos (ANAIS DO ENIC, 2023)
-